Analysis Shiga Toxin-Encoding Bacteriophage in a Rare Strain of Shiga Toxin-Producing Escherichia coli O157:H7 stx2a/stx2c - Greig, David R.; Mikhail, Amy F. W.; Dallman, Timothy J.; Jenkins, Claire (Frontiers in Microbiology, 2020)
In December 2015, five cases of Shiga toxin (Stx)-producing Escherichia coli (STEC) O157:H7 stx2a/stx2c phage type 24 were identified by the national gastrointestinal disease surveillance system at Public Health England. Frozen grated coconut imported from India was implicated as the vehicle of infection. Short and long read sequencing data were interrogated for genomic markers to provide evidence that the outbreak strain was from an imported source. The outbreak strain belonged to a sub-lineage (IIa) rare in domestically acquired infection in the United Kingdom, and indicative of an imported strain. Phylogenetic analysis identified the most closely related isolates to the outbreak strain were from cases reporting recent travel not to India, but to Uganda. Phylo-geographical signals based on travel data may be confounded by the failure of local and/or global monitoring systems to capture the full diversity of strains in a given country. This may be due to low prevalence strains circulating in-country under the surveillance radar, or a recent importation event involving the migration of animals and/or people. Comparison of stx2a-encoding prophage harboured by the outbreak strain with publicly available stx2a-encoding prophage sequences, revealed that it was most closely related to stx2a-encoding prophage acquired by STEC O157:H7 that caused the first outbreak of STEC-haemolytic uraemic syndrome in England in 1982-83. Animal and people migration events may facilitate the transfer of stx2a-encoding prophage from indigenous STEC O157:H7 to recently imported strains, or vice versa. Monitoring the global transmission of STEC O157:H7 and tracking the exchange of stx2a-encoding phage between imported and indigenous strains, may provide an early warning of emerging threats to public health.